Does quality child care centre shape children's behaviour? a case study of IIUM Educare - Janon, Nazariah Shar'ie (2012)
This paper discusses the role of child care centre in shaping children’s social behaviour. It hypothesizes that quality child care affects children’s social behaviour. More specifically, it is assumed that high quality child care will predict positive social behaviour in children. 100 parents of children aged 4 to 5 year old at the IIUM EDUCARE, Gombak participated in this study. Data were collected via survey and observations using measures such as the Early Childhood Environmental Rating Scale–Revised [ECERS-R ](Harms, Clifford, & Cryer, 1998), the Caregiver Interaction Scale [CIS] (Arnett, 1989), and the Adaptive Social Behaviour Inventory [ASBI] (Hogan, Scott & Bauer, 1992). Results indicated that the aspect of caregiver child interaction significantly associated with children social competency. Findings also suggested that the role of quality child care varied as a function of family variable. These results provide useful information in understanding the significant role of child care centre in child development.